An evaluation of modern tendencies in solving judo fights - Sterkowicz, S.; Maslej, P.
The aim of the work is to try to characterize time structure of judo fight and comparing the outcome of such research with previous researches (Sikorski 1985, Sterkowicz and Kesek 1985). We tried to trace the tendencies of changes in this field and use them for practical training postulates. 2. Material and Methods Research material comprised 92 video-recorded fights of seniors made during the 40th Individual Polish Senior Championship in Cracow (1996) and Polish Senior Individual-Team League in Bytom-City (1996). In those tournaments took part the leading Polish judoists: P.Nastula, R.Kubacki, K.Wojdan, P.Kamrowski, J.Lewak, M.Pitula. During the above mentioned championships there were recorded the whole fights including breaks during their time, in all weight categories starting from elimination round until the final round. In working out the outcome of the research basic statistical methods were used arithmetical average±standard deviation, and the percentage role of different factors. 3. Results On replaying the video of recorded fights the following results were obtained: 1. The time of the whole fight with all breaks (235,93±159,75s); 2. Time of the effective fight without breaks (174,42±110,17s). The index of using the maximal time of a fight, i.e. 5 min. was 58,3%. Owing the statistical analysis we found the noteworthy characteristics of pattern senior judoists bout: 1. Summarized time of breaks (61,51±59,4s); 2. Summarized time of fights in NE-WAZA (42,91±42,29s); 3. Summarized time of fights in TACHI-WAZA (131,55±87,96s). The typical time structure of senior judo contest has following numerical characteristics: 1. Single sequence of fight in NE-WAZA (15,79 ±14,26s, n = 250); 2. Single sequence of contest in TACHI-WAZA (18,9 ±13,16s, n = 640); 3. Single break (10,32 ±10,44s, n = 540). See Figure 2.